Genotoxic potential of the latex from cotton-leaf physicnut (Jatropha gossypiifolia L.) - Almeida, Pedro Marcos de; Araujo, Silvany de Sousa; Marin-Morales, Maria Aparecida [UNESP]; Benko-Iseppon, Ana Maria; Brasileiro-Vidal, Ana Christina (Soc Brasil Genetica, 2015)
Jatropha gossypiifolia L. (Euphorbiaceae), popularly known as cotton-leaf physicnut, is a milky shrub notable for its medicinal properties. The present study aimed to evaluate the toxic, cytotoxic and genotoxic effects of the latex of J. gossypiifolia, using Allium cepa L. as test system. Seeds of A. cepa were exposed to five concentrations of the latex (1.25; 2.5; 5; 10 and 20 mL/L) in order to evaluate parameters of toxicity (evaluation of root growth), cytotoxicity (mitotic index frequency) and genotoxicity (frequency of chromosome alterations). The latex showed a significant decrease in root mean growth value as well as mitotic index for the tested concentrations, except for 1.25 mL/L, when compared to results from the negative control. The 1.25, 2.5 and 5 mL/L concentrations induced significant chromosome adherences, C-metaphases and/or chromosome bridges, as genotoxic effects. The significant frequency of chromosome bridges also indicated mutagenic potential for chromosomes of J. gossypiifolia as discussed in the paper. Considering that the latex is used in popular therapies, and that the test system A. cepa presents good correlation with tests carried out in mammals, it can be pointed out that its use for medicinal purposes may be harmful to human health especially if ingested.
Keywords: Allium cepa test; Medicinal plant; Plant latex; Genotoxicity evaluation